2019
DOI: 10.3389/fimmu.2019.01637
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Circulating microRNA 101-3p in Type 1 Diabetes Patients: New Insights Into miRNA-Regulated Pathophysiological Pathways for Type 1 Diabetes

Abstract: MicroRNAs (miRs) are master regulators of post-transcriptional gene expression, and they are often dysregulated in individuals suffering from diabetes. We investigated the roles of miR-101-3p and miR-204-5p, both of which negatively regulate insulin secretion and cell survival and are highly expressed in pancreatic β cells, in the context of type 1 diabetes (T1D) pathogenesis. Using quantitative real time PCR, we evaluated serum levels of miR-101-3p and miR-204-5p in four groups, including recent-onset T1D pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…miR-378a-3p correlated negatively to IA2A and ZnT8A(Trp) but positively with GAD autoantibodies [17]. In a different autoantibody-positive cohort, miR-101-3p was elevated only in non-diabetic children with multiple autoantibodies and in children with recent-onset T1D and also correlated positively with GAD autoantibody levels [18]. In this cohort, miR-204-5p was elevated only in children with recent-onset T1D but not in non-diabetic autoantibody-positive children.…”
Section: Mirnas As Biomarkers In Type 1 Diabetes (T1d)mentioning
confidence: 90%
“…miR-378a-3p correlated negatively to IA2A and ZnT8A(Trp) but positively with GAD autoantibodies [17]. In a different autoantibody-positive cohort, miR-101-3p was elevated only in non-diabetic children with multiple autoantibodies and in children with recent-onset T1D and also correlated positively with GAD autoantibody levels [18]. In this cohort, miR-204-5p was elevated only in children with recent-onset T1D but not in non-diabetic autoantibody-positive children.…”
Section: Mirnas As Biomarkers In Type 1 Diabetes (T1d)mentioning
confidence: 90%
“…This process could be served as a new therapeutically tried target for T1DM [30,31]. matter that was largely analyzed by Santos A et al, who reported that the expression of miR-101 was about 3fold higher in patients with multiple autoantibodies level [32].…”
Section: Discussionmentioning
confidence: 99%
“…Zheng Y. and colleagues found that miR-101a is enriched in pancreatic cells and participates in β-cell dysfunction by decreasing the expression of antiapoptotic Bcl-2 and reducing pancreatic insulin secretion [30]. Higher circulating levels of miR-101-3p have also been reported to be associated with early-onset of T1D and T2D [31,32]. Therefore, the tissue expression of several miRNAs could be a consequence of a dynamic regulation of the rate of miRNAs produced and released into the circulation [4].…”
Section: Discussionmentioning
confidence: 99%